Psychological War in Vietnam: Governmentality at The United States Information Agency. Issue 3 (3rd July 2018) - Whyte, Jeffrey
ABSTRACT: The United States Information Agency (USIA) has received little sustained scrutiny from critical military geographers, despite the major role it played in waging the Cold War. This article outlines the USIA's role in waging psychological war in support of the US mission in Vietnam, notably its establishment in 1965 of the Joint United States Public Affairs Office (JUSPAO). Through an analysis of USIA operations, this article argues that psychological war can be understood as a governmental strategy to exert power over the people and territory of Vietnam. Through an examination of problems related to evaluating and conducting research for psychological war, this article questions the extent to which the United States succeeded in establishing this power, concluding that the effects of psychological war in Vietnam were, at best, inconclusive, and offer little evidence to support contemporary strategies to 'win hearts and minds'.